1982
DOI: 10.1007/bf00055997
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic interpretation of chromosomal and nuclear-DNA-content data in the genus Blennius (Blenniidae: Perciformes)

Abstract: The haploid DNA content and karyotypes of eight species of Blennius are studied. Six species had 2n = 48, two had 2n = 46.The karyotypes of these species have been compared with those of related species of the genus and it was suggested that pericentric inversions played an important role in the evolution of their karyotypes. No sex chromosomes were morphologically identifiable in these gonochorist species. The data are discussed in connection with possible lines of evolution within the genus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The diploid number obtained for B. trigloides (2n--48) is not coincident with 2n=46 assigned by Cano et al (1982), but it fully agrees with that reported by Cataudella & Civitelli (1975). For the rest of the species described earlier (Cataudella & Civitelli, 1975;Cano et al, 1982), the discrepancies only involve the chromosome morphology with the peculiarity that our results indicate a relatively higher proportion of biarmed chromosomes. These differences in chromosome characterization are very often found among studies of the same species by different authors.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The diploid number obtained for B. trigloides (2n--48) is not coincident with 2n=46 assigned by Cano et al (1982), but it fully agrees with that reported by Cataudella & Civitelli (1975). For the rest of the species described earlier (Cataudella & Civitelli, 1975;Cano et al, 1982), the discrepancies only involve the chromosome morphology with the peculiarity that our results indicate a relatively higher proportion of biarmed chromosomes. These differences in chromosome characterization are very often found among studies of the same species by different authors.…”
Section: Discussionsupporting
confidence: 79%
“…cannevae, B. pavo, B. ponticus incognitus, B. sanguinolentus, B. sphinx and B. trigloides. Three more species from the Mediterranean, B. gattorugine, B. ocellaris and B. pholis, were karyotypically described by Cano et aL (1982). The data shown in both reports indicate that, while the diploid number is fairly stable among the analyzed species (2n--48), there is a wide variation in the number of arms , although much of this variation may be most probably artificial, due to technical shortcomings.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations